Synthesis and Preliminary Characterization of Putative Anle138b-Centered PROTACs against α-Synuclein Aggregation - Martina Pedrini; Angelo Iannielli; Lorenzo Meneghelli; Daniele Passarella; Vania Broccoli; Pierfausto Seneci (MDPI AG, 2023)
The search for disease-modifying agents targeted against Parkinson's disease led us to rationally design a small array of six Anle138b-centered PROTACs, 7a,b, 8a,b and 9a,b, targeting αSynuclein (αSyn) aggregates for binding, polyubiquitination by the E3 ligase Cereblon (CRBN), and proteasomal degradation. Lenalidomide and thalidomide were used as CRBN ligands and coupled with amino- and azido Anle138b derivatives through flexible linkers and coupling reactions (amidation, 'click' chemistry). Four Anle138b-PROTACs, 8a,b and 9a,b, were characterized against in vitro αSyn aggregation, monitoring them in a Thioflavin T (ThT) fluorescence assay and in dopaminergic neurons derived from a set of isogenic pluripotent stem cell (iPSC) lines with SNCA multiplications. Native and seeded αSyn aggregation was determined with a new biosensor, and a partial correlation between αSyn aggregation, cellular dysfunctions, and neuronal survival was obtained. Anle138b-PROTAC 8a was characterized as the most promising αSyn aggregation inhibitor/degradation inducer, with potential usefulness against synucleinopathies and cancer.